Rice husk-based adsorbents for removing ammonia: Kinetics, thermodynamics and adsorption mechanism. Issue 4 (August 2021) - Bai, Wenli; Qian, Miaomiao; Li, Quanxiang; Atkinson, Steve; Tang, Bin; Zhu, Yanchao; Wang, Jinfeng
Abstract: Volatile organic compounds (VOCs) and odor are the main indoor air pollutants that can have impact on human health. In this study, the ammonia adsorption behaviors onto the three adsorbents from biomass rice husks, including silica carbon composite (RH-SiO2 -C), activated carbon (RH-AC) and silicon dioxide (RH-SiO2 ) were investigated by time-resolved infrared spectroscopy. It was found that 85% of the initial concentration was eliminated under the optimized conditions. The adsorption capacity of ammonia onto RH-SiO2 -C, RH-AC and RH-SiO2 at 298 K were found to be 7.28 mg g −1, 11.22 mg g −1 and 6.61 mg g −1, respectively. The pseudo-second-order model fit the kinetic data well for all the adsorbents and the adsorption rate constants were calculated. Thermodynamic activation parameters were obtained by studying the adsorption behavior at different temperatures, the activation energy values of ammonia adsorption onto RH-SiO2 -C, RH-AC and RH-SiO2 were calculated to be 38.80 kJ mol −1, 19.24 kJ mol −1 and 54.64 kJ mol −1, respectively. The activation enthalpy (ΔH # ), entropy (ΔS # ) and Gibbs free energy (ΔG # ) were also determined. Inverse gas chromatography (IGC), infrared spectroscopy (IR), X-ray photoelectron spectroscopy (XPS) and surface area experiment were conducted to propose possible adsorption mechanisms. Beside surface area related with porous structures, chemisorption based on Lewis acid-base reaction may be a crucial interaction between ammonia and the adsorbents. This study gains insights into the adsorption of ammonia onto the biomass rice husk-based adsorbents, which inspires the further design of adsorbents to effectively remove VOCs and odors, therefore achieving a high efficiency for air pollution control. Graphical Abstract: ga1 Highlights: Three different adsorbents were obtained from biomass rice husks. Dynamic adsorption behaviors of ammonia onto rice husk-based adsorbents were investigated. Ammonia adsorption onto the three adsorbents all follows the pseudo-second-order model. Activation parameters for interaction between ammonia and adsorbents are obtained. Both porous structure and surface chemistry determine ammonia adsorption performance.